Shared decision-making in Cervical Cancer Care at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A mixed-methods study - Sosina Workineh Tilahun; Adiam Nega; Lealem Wagaw; Adamu Addissie (PLoS ONE, 2026)
Background Shared decision-making is crucial for alignment of treatment options with patient values and preferences. However, currently in Ethiopia, shared decision-making in clinical care of cancer, in which cervical cancer is not exceptional, is not well understood. Aim This study aimed to assess the perceived level of shared decision-making and its predictors in cervical cancer care at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia. Methods We employed a convergent parallel mixed-methods study design from February 18 to May 23, 2025, at Tikur Anbessa Specialized Hospital. The study used interviewer-administered questionnaires for 203 cervical cancer patients and in-depth interviews for 15 cervical cancer patients and 10 clinical oncologists. Using SPSS v26, multiple linear regression analysis was used to determine significant predictors of the perceived level of shared decision-making, with statistical significance set at P < 0.05. Thematic analysis was conducted for the qualitative data. Results The overall mean score for the perceived level of shared decision-making was 24.94 (± 9.12), with a range of 7–44, and the standardized mean score was 2.77 (± 1.01). The perceived level of shared decision-making had positive linear associations with increased trust in oncologists (0.32, 95% CI (0.21, 0.44); p < 0.001). Conversely, it had negative linear associations with rural residential area (−2.94, 95% CI (−5.34, −0.54); p = 0.02), unemployment status (−4.36, 95% CI (−6.96, −1.76); p = 0.001), and higher health literacy score (−6.89, 95% CI (−9.92–-3.86); p < 0.001). Thematic analysis revealed contextual, cultural, relational, institutional, and communicational factors influencing shared decision-making practice in cervical cancer care. Conclusions The study emphasized the complex interplay of factors influencing the practice of shared decision-making in clinical care of cervical cancer. Therefore, understanding these dynamics may help to enhance the practice of shared decision-making in clinical cervical cancer care.